Sistema Web Gestor en Seguimiento y Control de Grupos, Investigadores y Productos en el Área de Investigación de la Universidad Nacional de Loja. - Paredes Córdova, Carlos Augusto (2023)
Nowadays, in the academic context, the efficient management of research projects has become a critical factor for educational institutions. As a straight response to this need, this thesis research work focuses on implementing a web-based system designed to streamline the monitoring and control of research projects at UNL. The execution of this project was broken down into three phases. Firstly, the BPM RAD methodology was applied in order to clarify and define the current process of monitoring and control of research projects of the UNL Research Department. Through this modeling, a diagram was obtained that visually represents the state of the current process. In addition, a second diagram representing the automation of the monitoring and control of research projects (SPI) was developed. In the second phase, the XP methodology was adopted together with the Scrum Framework and the 4+1 architectural model, designated by the Department of Information Technologies of the UNL, where the complete implementation of an operative web system designed for the monitoring and control of research projects of the UNL was achieved, to later test it in a controlled environment. Finally, in the third phase, a test plan was developed where a specific set of tests were defined to be executed, evaluating both the performance and the functionality of the software. The results obtained showed that the implemented functionalities satisfactorily met the requirements established by the client. This achievement has enriched the quality of information available, improving strategic decision making, providing researchers and system managers with greater visibility of the procedures, promoting a clearer and more detailed understanding of the system. Keywords: monitoring, control, projects, XP methodology, automation.